Isavuconazole as initial antifungal therapy combined with surgical management of pediatric pulmonary mucormycosis: a case report and literature review - Sun, Yao; Yuan, Lihua; Hu, Tianjiao; Sun, Chuan; Yang, Dandan; Tian, Man; Dong, Shichao; Gu, Haiyan (Frontiers in Pediatrics, 2026)
Invasive mucormycosis (IM) in pediatric patients is a rare but life-threatening fungal disease with limited treatment options. Isavuconazole is a new triazole that has shown efficacy and safety in adults for both primary and salvage treatment of mucormycosis. However, data regarding the initial use of isavuconazole in children are rare. In this study, we report a case of a 6-year-old girl with diabetes mellitus. Metagenomic next-generation sequencing detected Rhizopus oryzae in her bronchoalveolar lavage fluid , and a chest computed tomography revealed a reversed halo sign. Oral isavuconazole was given as primary monotherapy with continuous control of blood glucose. After the lesion partially shrank and became confined, the patient visited the thoracic surgery department to undergo lobectomy; she recovered well after the procedure. This report highlights the importance of quick diagnosis of mucormycosis and may provide a reference for providing the initial antifungal treatment in pediatric mucormycosis. All of the aforementioned interventions helped buy time for subsequent surgical treatment, leading to the curing of the child. Isavuconazole may represent an effective and safe therapeutic option as first-line monotherapy for pediatric mucormycosis.